MENELAAH TAFSIR QS. AN-NISA:114 (STUDI TENTANG DAKWAH PERSONAL/FARDIYAH) - Suhartini (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
Currently, some people have the wrong mindset of da'wah, that da'wah is only limited to advice and warnings, dhikr and jihad, tabligh and bayan only. They limit their big and broad meaning. As a result, the influence of da'wah weakens and cannot enforce Islam throughout the earth. Learn QS. An-Nisa: 114 by using the Tafsir of the Qur'an bil Qur'n to correct this erroneous understanding. Learn QS. Al-Nisa:114 teaches how da'wah covers various aspects of human life for the establishment of Dienul Islam. Da'wah which includes various aspects is carried out personally without neglecting da'wah in tabligh to the public. Qs.An-Nisa:114 teaches da'i to establish close relationships with the object of their da'wah so that aspects that cannot be touched by tabligh da'wah can be done such as economic improvement, ishlah (fixing conflicts between individuals or groups). This Ayah also teaches da'i not to be busy preaching to the community but also to pay attention to themselves and their families so that the order of community and state life can be upheld with Islamic values.